2022
DOI: 10.1007/s00586-021-07093-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and agreement of national spine register data for 474 patients compared to corresponding electronic patient records

Abstract: Purpose Data quality is essential for all types of research, including health registers. However, data quality is rarely reported. We aimed to assess the accuracy of data in a national spine register (NORspine) and its agreement with corresponding data in electronic patient records (EPR). Methods We compared data in NORspine registry against data in (EPR) for 474 patients operated for spinal stenosis in 2015 and 2016 at four public hospitals, using EPR as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Therefore, the registration of relevant comorbidities by the treating surgeon may be questioned. A validation study of NORspine data found that surgeons tended to underreport relevant comorbidities and that ASA grading done by the anesthetist could be more reliable in assessing comorbidity [ 20 ]. In our study, there was no difference in the proportions of ASA grades 1 and 2 patients among non-respondents compared to respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the registration of relevant comorbidities by the treating surgeon may be questioned. A validation study of NORspine data found that surgeons tended to underreport relevant comorbidities and that ASA grading done by the anesthetist could be more reliable in assessing comorbidity [ 20 ]. In our study, there was no difference in the proportions of ASA grades 1 and 2 patients among non-respondents compared to respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The DWG registry does not require documentation of the final histopathological diagnosis, which might solve this problem. Furthermore, underreporting of complications has been observed previously 10 and complication rates of 12.0% (redon) respective 8.5% (no redon) seem to be unexpectedly low within this vulnerable collective of tumor patients 11 .…”
Section: Discussionmentioning
confidence: 61%
“…The second aim was to register other underlying diseases, which can negatively affect the course or treatment of the disease. In comparison to similar registry systems such as NOR spine 12 and Spine Tango, 11 more data elements have been considered for registering the disease risk factors. For example, in Spine Tango, height, weight, and cigarette smoking had been considered as risk factors 11…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, some registry systems have been created in recent years in different countries for registering vertebral column disorders, such as spinal canal stenosis. The examples include (NOR spine) 11,12 and the Swedish spine register (Swespine). 13 One of the most essential stages in designing a registry system related to a special disease is determining it's minimum data set (MDS).…”
mentioning
confidence: 99%